Genotipagem e aspectos filogenéticos e evolutivos de Pythium insidiosum - Weiblen, Carla (2019)
Oomycetes are eukaryote microorganisms belonging to a supergroup called Stramenopiles-Alveolata-Rhizaria (SAR) that includes members with saprobic and pathogenic characteristics. Pythium insidiosum, a pathogen of plants and mammals, stands out among the genera of major importance in the peronosporalean lineage. Pythiosis is a chronic granulomatous disease with an unfavorable prognosis, widely distributed throughout the world. In recent years, there has been an increase in cases of pythiosis, especially in animals and humans, and Brazil and Thailand, respectively. It should be noted that many gaps in knowledge about important aspects of this disease must be fulfilled, especially in relation to the biology and evolution of the etiological agent, epidemiology, diagnosis and therapy. Thus, the objectives of the study are: (i) to use polymerase chain reaction (PCR) based on single nucleotide polymorphisms (SNPs) of ribosomal DNA sequence (rDNA) to identify and genotype South American isolates of P. insidiosum and (ii) to analyze phylogenetic relationships and evolutionary aspects of peronosporaleans, especially P. insidiosum using a multilocus approach with one mitrocondrial gene and three nuclear genes. Objective (i) was achieved through the identification of P. insidiosum by the PCR-multiplex technique based on three SNPs. In addition, the method allowed to identify the formation of three clades of P. insidiosum (clade I: American isolates, including for the first time, a Uruguayan isolate, clade II: Thai, Japanese and Indian isolates and clade III: Thai isolates). The results that encompass objective (ii) correspond to the multilocus analysis of 55 oomycetes by the Maximum Likelihood and Bayesian Analysis methods. P. insidiosum formed a major monophyletic and polytomic clade of American isolates; however, Pythium spp. was paraphyletic with Phytopythium sp. and Phytophthora spp. Albugo candida was positioned as an initial branch of peronosporaleans, which was subdivided into three clades, one of which evidenced the close relationship of P. insidiosum, P. aphanidermatum and P. arrhenomanes. Peronosporaleans diverged 136 million years ago and P. insidiosum diversified approximately 24 million years ago, with the divergence of American and Thai isolates, approximately 17 million years ago and subsequent American diversification occurring there are 2.4 million years ago. The reconstruction of the ancestral state characterizes that the ancestors of peronosporaleans presented phytopathogenic properties, with the ancestors of Pythium + Phytopythium + Phythophthora presenting necrotrophic properties. The applicability of the multiplex-PCR for identification and genotyping of the South American isolates of P. insidiosum, which showed similar genetic characteristics among these isolates, was concluded in this thesis. In addition, the multilocus analysis allowed verifying phylogenetic relationships and important evolutionary aspects of oomycetes, emphasizing P. insidiosum.